Experimental measurements of carbon dioxide, methane and nitrogen high-pressure adsorption properties onto Malaysian coals under various conditions - Abunowara, M. (Elsevier Ltd, 2020)
In this study, the CO2 adsorption capacity was measured on Malaysian sub-bituminous coals in dry and moisture equilibrated state using volumetric technique to understand its carbon sequestration and storage potential. The CO2 adsorption capacity onto dry and wet coal samples was performed at 300â348 K and 6 MPa. Four coal specimens, namely S1, S2, S3 and S4 were analysed by using BET, XRD and FESEM techniques before and after CO2 adsorption. The dry S3 coal had showed the highest CO2 adsorption capacity 1.59 mmol gâ1 at 300 K and 6 MPa among all samples. FTIR spectra patterns explain this behaviour as they showed an excessive presence of hydroxyl and carboxyl functional groups in dry coal samples. The functional group analysis of all the wet coal samples exposed to CO2 showed significantly declined adsorption relative to their corresponding dry samples. The mineral phases were identified within all fresh and wet exposed coal samples to CO2 through XRD analysis. The S3 coal had the highest selectivity of CO2 over CH4 and N2 gases at pressures up to 6 MPa. The bituminous Malaysian coal has a high affinity to adsorb CO2 in dry and wet conditions. Â© 2020 Elsevier Ltd